Por un materialismo de la infancia. Una lectura de Las cosas de Arnaldo Antunes - Canseco, Adriana (Universidad Nacional del Litoral, 2020)
In this work we will think about a «materialism of infancy» in Las cosas of Arnarldo Antunes. The editorial characteristics of the book allow us to observe in the relationship between image and writing, the «infantile» characteristic of the book. The concept of the apocryphal language of Jean-Luc Nancy will be central to determine the implications of this sense of infancy. This concept of infancy as a limit between language and experience will put at stake the body as tactile memory (Barthes) that builds the material territory of writing. This exercise of language will make us wonder how poetry plays in the limit that take the language to the extreme of itself.